Three hot-Jupiters on the upper edge of the mass–radius distribution: WASP-177, WASP-181, and WASP-183. Issue 4 (14th March 2019) - Turner, Oliver D; Anderson, D R; Barkaoui, K; Bouchy, F; Benkhaldoun, Z; Brown, D J A; Burdanov, A; Collier Cameron, A; Ducrot, E; Gillon, M; Hellier, C; Jehin, E; et al.
ABSTRACT: We present the discovery of three transiting planets from the WASP survey, two hot-Jupiters: WASP-177 b (∼0.5 MJup, ∼1.6 RJup ) in a 3.07-d orbit of a V  = 12.6 K2 star, WASP-183 b (∼0.5 MJup, ∼1.5 RJup ) in a 4.11-d orbit of a V  = 12.8 G9/K0 star; and one hot-Saturn planet WASP-181 b (∼0.3 MJup, ∼1.2 RJup ) in a 4.52-d orbit of a V  = 12.9 G2 star. Each planet is close to the upper bound of mass–radius space and has a scaled semimajor axis, a / R *, between 9.6 and 12.1. These lie in the transition between systems that tend to be in orbits that are well aligned with their host-star's spin and those that show a higher dispersion.